Syndecans, cell surface heparan sulfate proteoglycans, are induced by a proline-rich antimicrobial peptide from wounds. - Gallo, R L (1994)
Cell surface heparan sulfate proteoglycans, such as the syndecans, are required for cellular responses to heparin-binding growth factors and extracellular matrix components. Expression of syndecan-1 and -4 is induced in mesenchymal cells during wound repair in the mouse, consistent with a role for syndecans in regulating cell proliferation and migration in response to these effectors. Here we show that wound fluid contains inductive activity that mimics the in vivo induction in time of appearance, specificity for mesenchymal cells, and selectivity for syndecan-1 and -4. We have purified and synthesized a 4.8-kDa proline-rich protein from wound fluid that reproduces this induction of syndecan-1 and -4 in cultured cells. This peptide, identical to the antibacterial peptide PR-39, is released into the wound by the cellular infiltrate and induces syndecan expression at the same peptide concentrations that lyse bacteria. These results indicate that wounds contain a multifunctional protein that induces mammalian cells to express cell surface heparan sulfate proteoglycans as part of the wound repair process and that kills bacteria as part of a nonimmune defense mechanism.